Synthesis of enantiopure glycidol derivatives via a one-pot two-step enzymatic cascade. Issue 7 (22nd December 2014) - Liu, Yu-Chang; Liu, Yan; Wu, Zhong-Liu
Abstract : An enzymatic cascade reaction employing an S -specific ketoreductase and a styrene monooxygenase to synthesize enantiopure glycidol derivatives is described. Abstract : Styrene monooxygenase (SMO) can catalyze the kinetic resolution of secondary allylic alcohols to provide enantiopure glycidol derivatives. To overcome the low theoretical yield of kinetic resolution, we designed a one-pot two-step enzymatic cascade using prochiral α, β-unsaturated ketones as the substrates. An S -specific ketoreductase Ch KRED03 was screened for the efficient bioreduction of the substrates to provide ( S )-allylic alcohols, which underwent SMO-catalyzed epoxidation to achieve glycidol derivatives with contiguous stereogenic centers. Excellent enantioselectivity (ee > 99%) and diastereoselectivity (de > 99%) were achieved for the majority of the substrates, and product yields reached up to >99%.